36+32=13-(x-3)

Simple and best practice solution for 36+32=13-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+32=13-(x-3) equation:


Simplifying
36 + 32 = 13 + -1(x + -3)

Combine like terms: 36 + 32 = 68
68 = 13 + -1(x + -3)

Reorder the terms:
68 = 13 + -1(-3 + x)
68 = 13 + (-3 * -1 + x * -1)
68 = 13 + (3 + -1x)

Combine like terms: 13 + 3 = 16
68 = 16 + -1x

Solving
68 = 16 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
68 + x = 16 + -1x + x

Combine like terms: -1x + x = 0
68 + x = 16 + 0
68 + x = 16

Add '-68' to each side of the equation.
68 + -68 + x = 16 + -68

Combine like terms: 68 + -68 = 0
0 + x = 16 + -68
x = 16 + -68

Combine like terms: 16 + -68 = -52
x = -52

Simplifying
x = -52

See similar equations:

| 7r+2=5(r-4)whatisx | | 5x(3x+5)=10 | | w=21+2p | | 3.2x+14=-4 | | 163.2+23.84x-16x^2=4 | | 5x(3x+5)=5 | | 5=5a | | 12rs+5r-6s= | | x^2-490x+5000=0 | | 5+4b=20 | | 9-6x=26 | | 3y-2=5y+6 | | -3(4+6n)-7=8n-7-14 | | -5n-6+4n=-14 | | -6(y-2)=2y-24 | | -6(7-2)=2y-24 | | 6=2+d | | -5u-46=-8(u+8) | | Y-2=2.6(x-0) | | 45-(4-2y-4(y+7))=-4(1+3y)-(4-3(y+2)-2(2y-5)) | | -11+x=-7x-8(x+1) | | -37+7=-9y+49 | | -37+7=-97+49 | | 10x-30+7x=13x | | 13-3v=8v+2 | | -5v+8(v+3)=39 | | 7x^2+16x=192 | | 3(w-8)+3w=-18 | | 18n-24t= | | 7=3y+y-8 | | 6(y+3)+2y=-38 | | X-2+x-3=123 |

Equations solver categories